Identification of auxin response factor SlARF8-1 gene and characterization of expression pattern of some SlARFs in Solanum lycopersicum - WANG Fei-yan; WU Jian; ZHANG Jia-jing; CHENG Lin; KONG Fu-ling; PENG Zhen; LU Gang (浙江大学学报. 农业与生命科学版)
The full-length cDNA sequence of a new auxin response factor family gene with an open reading frame (ORF) of 2 535 bp in length was cloned, encoding a protein of 844 amino acids that was 94% homologous with SlARF8, and this new gene located on different chromosomes with SlARF8 based on tomato genome data, so it was named SlARF8-1 (GenBank accession number HM560979). Then the temporal and spatial expression patterns of four ARFs genes (SlARF3, SlARF4, SlARF6 and SlARF8-1) were analyzed in tomato stems, leaves, ovaries and fruits at different development stage using semi-quantitative RT-PCR. The results showed that SlARF8-1 was expressed in all tissues examined, but at a lower level in the ovary after pollination. By contrast, the transcripts of SlARF3 and SlARF6 were undetectable in leaf and ovary. These four SlARFs genes showed similar expression pattern at different stages of tomato fruit development. Furthermore, the SlARFs mRNAs levels in tomato fruits didn t change significantly after the ovaries were treated with exogenous hormones of 2, 4- dichlorophenoxyacetic acid (2, 4-D) and gibberellic acid (GA3), which could induce significantly parthenocarpic fruits in tomato.